2015
DOI: 10.3390/ijerph120100554
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus and Impaired Fasting Glucose, Associated with Risk Factors in Rural Kazakh Adults in Xinjiang, China

Abstract: Objective: This study aimed to estimate the prevalence of diabetes mellitus (DM) and impaired fasting glucose (IFG) in a Kazakh population aged ≥18 years living in the YiLi District of Xinjiang, China and to evaluate the associated risk factors of diabetes. Methods: Randomly selected adults, living for at least 6 months in the YiLi District in Xinjiang had their clinical characteristics and standard blood chemistries measured. DM and IFG were defined according to WHO 1999 criteria. The adjusted odds ratio (ORs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
26
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 17 publications
9
26
3
1
Order By: Relevance
“…In the multivariate logistic regression analysis, we found that high BMI, hypertension, and elevated TG were significantly associated with an increased risk of pre-diabetes, which was consistent with the study conducted by Li et al [7]. Song et al [26] found that there were interactions between age ≥45 years, obesity, high-fat diet, and low educational level, and they proposed that screening and early intervention in people with a family history of diabetes and obesity was crucial to reduce the risk of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…In the multivariate logistic regression analysis, we found that high BMI, hypertension, and elevated TG were significantly associated with an increased risk of pre-diabetes, which was consistent with the study conducted by Li et al [7]. Song et al [26] found that there were interactions between age ≥45 years, obesity, high-fat diet, and low educational level, and they proposed that screening and early intervention in people with a family history of diabetes and obesity was crucial to reduce the risk of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…The exact reason for the discrepancy is unclear, more consumption of meat and dairy foods by the residents in Xinjiang than other regions of mainland of China may be a potential factor. Compared to Han and Uygur Chinese, Kazakh consumed more dairy products but the prevalence was not the lowest, and one of the possible explanation may be along with higher consumption of meat and less vegetables and fruits [58]. We also found ethnic difference of lipid levels among Han, Uygur and Kazakh populations.…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, the overall prevalence of diabetes among four unique ethnic groups in Yunnan Province was found to be lower than the national average in 2010 [5], as well as lower than other ethnic populations in China, such as Kazakh (5.9%) [17], She (6.1%) [18], Manchu (8.39%) and Korean Chinese (9.42%) [7]. This disparity in prevalence could be explained by differences in dietary habits, lifestyle, income level and genetic backgrounds.…”
Section: Discussionmentioning
confidence: 64%